2017
DOI: 10.1177/1461445617706999
|View full text |Cite
|
Sign up to set email alerts
|

Enquiry calls to GP surgeries in the United Kingdom: Expressions of incomplete service and dissatisfaction in closing sequences

Abstract: Kingdom. Using conversation analysis, combined with coding of 447 calls, we studied the role of thank you in closing sequences, focussing on their timing and order in relation to service outcome. We show, first of all, how patients withhold thank you in orientation to an absent summary or specification of service:patients are more likely to initiate thank you if the receptionist volunteers such a summary. Secondly, we show there is variation in how appropriately participants project the termination of calls us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Pre-closing work involves providing for additional matters to be raised before termination, so that participants are aligned at the moment of closing. For example, displays of appreciation are a common feature in closing environments in both mundane and institutional settings (Antaki 2002;Sikveland and Stokoe 2017;Woods, Drew, and Leydon 2015). Other common features are summarizing what has been said or orienting to future action or arrangements (e.g., Button 1987; Patterson and Potter 2009;Robinson 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-closing work involves providing for additional matters to be raised before termination, so that participants are aligned at the moment of closing. For example, displays of appreciation are a common feature in closing environments in both mundane and institutional settings (Antaki 2002;Sikveland and Stokoe 2017;Woods, Drew, and Leydon 2015). Other common features are summarizing what has been said or orienting to future action or arrangements (e.g., Button 1987; Patterson and Potter 2009;Robinson 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, closing a phone call runs the risk of suggesting that the person is not so interested in the other person and such possible inferences may, therefore, need to be managed as part of pre-closing. Meanwhile, in closing service encounters, participants tend to deal with the extent to which relevant service has in fact been delivered (Sikveland and Stokoe 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(line 17) and hangs up without producing a greeting and without waiting for an answer from his interlocutor. Note how here, as in other service encounters that end unsatisfactorily (Aston, 1995;Sikveland & Stokoe, 2017), 'thank you' is not used as a token of appreciation or a display of satisfaction, but as a resource for expediting conversational closure.…”
Section: Closing the Callmentioning
confidence: 99%
“…The TCU closes off the on-going sequence with a positive assessment 'would be great to talk to you: about that' (lines 5-6). It then continues with two closing implicative moves (Button, 1987;Sikveland & Stokoe, 2017): (1) a reiteration of the already agreed plan to send the prospect an Outlook invitation and (2) a reminder of the time and date of the meeting. The prospect sustains the call's closing trajectory by producing a combination of assessments (the object-side 'Lovely' followed by a subject-side assessment 'Look forward to seeing it' in line 11) which can be heard as 'complete' (Edwards & Potter, 2017).…”
Section: Closing the Callmentioning
confidence: 99%
“…Teas Gill & Roberts, 2012) yet only a handful of studies investigate the position and work of medical receptionists. Fewer still ask how they do their jobs (Sikveland & Stokoe, 2017a, 2017bSikveland, Stokoe, Demjen, 2019;. What little research does exist has not always presented receptionists favourably but has suggested that receptionists are impersonal gate-keepers who withhold access to care (Arber & Sawyer, 1985;Hewitt, McCloughan, & McKinstry, 2009).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%